Pengaruh Education First Aid (E-Fa) Game terhadap Pengetahuan Layperson Pertolongan Pertama Cedera Pada Anak Usia Sekolah - Nastiti, Eky Madyaning; Darotin, Rida (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Injuries can affect anyone, including school-age children, and are often caused by a lack of understanding of injury concepts, insufficient knowledge of first aid, and unsafe environments. Therefore, it is crucial to provide first aid and health education to promote overall health and safety. The E-Fa (Education First Aid) Game is a novel approach presented as a game-based Android application. The aim of this study is to analyze the differences in students' knowledge improvement regarding injury management. The study design employed a quasi-experimental approach with a one-group pretest-posttest design. Fifty-one respondents were selected through simple random sampling techniques. Data collection involved the use of questionnaires to measure knowledge variables before and after the intervention with the E-Fa Game. The research was conducted at SMP 12 Jember. Data analysis was performed using the Wilcoxon test. The results revealed that students' knowledge of performing first aid for injuries improved significantly. The average score increased from 5.90 during the pretest to 7.04 during the posttest, with a p-value of 0.000, indicating a significant improvement in knowledge among SMP 12 Jember students in handling injuries after receiving the intervention with the E-Fa Game. This study demonstrates the effectiveness of the E-Fa Game in enhancing schoolchildren's knowledge of injury management.